Correlation between Nurses’ Behavior and Ability to Perform Fluid-and Electrolyte-Related Nursing Diagnoses - Kamayani, Made Oka Ari; Nurhesti, Putu Oka Yuli; Suardana, I Wayan (Journal of A Sustainable Global South; Vol 7 No 2 (2023): August 2023, 2023)
Fluids and electrolytes are one of the basic human needs. Imbalance of fluids and electrolytes in the body can cause disturbances in various body systems. Nurses play a major role in fluid and electrolyte management of patients. Proper management will provide optimal results for the patient. This study aims to determine the correlation between nurses’ competence (knowledge, attitude, practice) and the ability to perform fluid- and electrolyte-related nursing diagnoses. This cross-sectional research analysed data collected using questionnaires from July to August 2021. The survey involved 65 nurses at Bangli Hospital, asking about socio-demographics, competence proxied by knowledge, attitude, and practice, and the ability to perform patients' fluid- and electrolyte-related diagnoses. Data were analysed using a Spearman Rank. The average value of knowledge was 16.46 (score 0-20), attitude 43.06 (score 10-50), practice 46.50 (score 10-50), and the average rating of the ability to perform diagnoses was 14.06 (score 5-20). The Spearman Rank test results show that knowledge correlates to the ability to perform diagnoses with a p-value of 0.57, attitude p= 0.04, r= 0, 251, and practice p= 0.75. The study results show a positive correlation between competence and the ability to perform diagnoses. Efforts are needed to improve nurses’ abilities in performing fluid- and electrolyte-related diagnoses.